Bis(1-benzo[d]triazolyl)oxalate and Bis(1-benzo[d]triazolyl)carbonate as Potential Explosive Compounds - Oskar Keller; Walter Graf (CHIMIA)
The two diesters (1 and 2) mentioned in the title are very shock sensitive in dry state. They can be stabilized by adding 30% of 1,1,2-trichloroethane.